Relevansi Fungsi Gatekeeper di Era Gempuran Media Sosial - Melati Budi Srikandi (Jurnal Ilmiah Komunikasi (JIKOM) STIKOM IMA, 2023)
The main key component in presenting information in the mass media is the gatekeeper. Gatekeeper is the spearhead of information before it is finally applied to the mass media. Gatekeepers are also responsible for ensuring that the information to be conveyed is quality information, believed to be true, feasible, and indeed important to convey to the public. Meanwhile, the presence of social media makes the existence of gatekeepers pseudoscientific. Social media that can be operated by any individual without having a specific institution is of particular concern. This research was conducted using a literature study approach by reviewing previous research. The data presented focuses on a systematic explanation of the facts obtained about the literature review and the results of previous studies that have relevance to this study. As a result, the Gatekeeper Function in today's era of social media exposure finds its relevance to the audience's active involvement in selecting and filtering the information they upload or will receive directly. In addition, the gatekeeper function carried out by social media refers to a design that is taken in the process of filtering information for the audience through codes that have been formulated in each platform. Codes are taken or decided through a screening process carried out by internal media parties taking into account community values and norms.